Effect of monosodium glutamate on testicular tissue of paclitaxel-treated mice: An experimental study - Davoud Kianifard; Ali Ehsani; Parisa Zeinolabedini Daneshgar; Ghasem Akbari; Seyyed Maysam Mousavi Shoar4 Ph.D. Candidate (Shahid Sadoughi University of Medical Sciences, 2019)
Background Paclitaxel (PTX), a chemotherapeutic agent, and monosodium glutamate (MSG) have oxidative effects on testicular tissue. Objective In this study, the effects of MSG administration on the exacerbation of testicular tissue alterations related to PTX treatment were evaluated. Materials and Methods MSG (30 & 60 mg/kg i.p.) was administrated to six groups (n = 8/each) of adult mice before or after PTX treatment: control, PTX-treated, MSG30 + PTX, MSG60 + PTX, PTX + MSG30, and PTX + MSG60. Following the euthanizing, the body weight measurement, pituitary-testicular axis hormonal analysis and serum lipid peroxidation index assessment was prepared, testicular histomorphometry (tubular diameter and germinal epithelium height), immunohistochemistry of p53 was completed. Microscopic indices of spermatogenesis (tubular differentiation, spermiogenesis and repopulation indices) were studied. Results Body weight was not changed significantly. The levels of testosterone (p = 0.0001), follicle stimulating hormone (p = 0.019), and luteinizing hormone (p = 0.08) were decreased while the level of lipid peroxidation index was increased (p = 0.208) in the treated groups. The histomorphometry indices (p < 0.0001 and p = 0.001, respectively), germ cells population (p < 0.05) and microscopic indices of spermatogenesis (p = 0.001, p = 0.005, p < 0.0001, respectively) were significantly reduced in all treated groups. The administration of MSG before PTX treatment induces more changes. The most positive reaction to p53 was observed in MSG30 or 60 + PTX groups compared to other groups. Conclusion The administration of MSG could intensify testicular tissue alterations related to PTX chemotherapy.